The Influence of Pressure to Mechanical Properties Dendrocalamus Asper Blade - Iskandar Yasin (Department of Civil Engineering, Faculty of Engineer, Universitas Sarjanawiyata Tamansiswa, 2016)
Bamboo laminated substitute wood for construction materials. To create a bamboo lamination beam made by compression. The bamboo used in this work belongs to the species of Bambusa Dendrocalamus asper (local name: bambu Petung). The purpose of this study was to determine the influent of pressure to mechanical properties bamboo blade. the dimensions of objects based on standard iso 2004. Testing of physical properties include moisture content and density, mechanical properties testing include compressive strength, tensile strength, shear strength and flexural strength. Bamboo 6-year-old tested. Each specimen compressed by pressure variations 0 MPa, 1.5 MPa, 2 MPa and 2.5 MPa. The results of mechanical properties testing conducted correlation with statistical analysis. Observation by Scanning Electron Microscopy to determine the damage to the bamboo fiber.